Particulate plastics in terrestrial and aquatic environments - Bolan, Nanthi; Kirkham, M. B.; Halsband, Claudia; Nugegoda, Dayanthi; Ok, Yŏng-sik, 1944- (Boca Raton : CRC Press, 2020)
"Particulate Plastics in Terrestrial and Aquatic Environments provides a fundamental understanding of the sources of these plastics and the threats they pose to the environment. It demonstrates the ecotoxicity of particulate plastics using case studies and offers management practices to mitigate environmental contamination"--
OCLC-licensed vendor bibliographic record.
Keywords: Microplastics -- Environmental aspects; Pollution prevention; NATURE / Ecology; SCIENCE / Environmental Science; SCIENCE / Life Sciences / Zoology / General